Réponse à Marjolijn Verspoor : de la nécessité d’aller au-delà du linguistique - Jean-Paul Narcy-Combes (Recherches en didactique des langues et des cultures)
This article has an unusual format as its author responds to another article in the same issue that relates the exchanges that took place during a Notion in Question (NEQ) seminar devoted to « Emergentism » in January 2016. The theoretical position of the respondent, a researcher in language learning and teaching, justifies his response. The first part of the article will describe this transdisciplinary position in which emergentism has a place in a plurilingual perspective. The second part is as much a response to Marjolijn’s Verspoor (MV)’s contribution as to the debates on that day. The results of MV’s research are rich and worthwhile but their very limitations justify the need for transdisciplinary collaboration in which the various fields of research complement each other.